2008
DOI: 10.1002/jmri.21607
|View full text |Cite
|
Sign up to set email alerts
|

Novel technique used to detect swallowing in volume‐selective turbo spin‐echo (TSE) for carotid artery wall imaging

Abstract: Purpose: To improve three-dimensional (3D) volume-selective turbo spin-echo (TSE) carotid wall imaging by the addition of a novel body surface swallowing detection device. Material and Methods:A 3D volume-selective TSE sequence was used to image the carotid artery. A novel carbon-fiber motion device, positioned over the laryngeal prominence, was used to detect swallowing movement. An electrical output generated by coil movement was used to detect motion, and an algorithm was programmed to reject data acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…However, it should be pointed out that the image quality obtained from the SPACE SWL + SG scan is slightly inferior to that obtained from the “SPACE STIL” scan and the difference was statistically significant. This could potentially be attributed to heart‐rate variability‐induced artifacts that commonly follows swallowing (14); variable T 1 recovery between echo trains would introduce signal modulation and thus image blurring. Discarding data collected several TRs right before and after the detection of swallowing may help reduce image degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be pointed out that the image quality obtained from the SPACE SWL + SG scan is slightly inferior to that obtained from the “SPACE STIL” scan and the difference was statistically significant. This could potentially be attributed to heart‐rate variability‐induced artifacts that commonly follows swallowing (14); variable T 1 recovery between echo trains would introduce signal modulation and thus image blurring. Discarding data collected several TRs right before and after the detection of swallowing may help reduce image degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Navigator echoes acquired from the epiglottis can be used to eliminate data acquired during swallowing, but it requires precise placement of navigator bars and may fail when the epiglottis shifts (13). Recently, Chan et al applied a MR‐safe coil made from carbon fiber to detect swallowing‐related motion at the laryngeal prominence (14). However, additional setup time of up to 15 min for the hardware including coil positioning and preamplifier parameters tune‐up can markedly prolong scanning.…”
mentioning
confidence: 99%
“…Other than navigator based techniques, external coils that can accurately detect neck motion have also been proposed for improved carotid artery image quality. In an in vivo study on five healthy volunteers, the adoption of the external coil was found to significantly improve the image quality and minimize swallowing artifacts (46) (Fig. 3).…”
Section: Plaque Burden Measurementsmentioning
confidence: 99%
“…The related motion sensitized driven equilibrium (MSDE) technique for blood suppression [45] has also been investigated for use in a 3D protocol because it does not depend on inflow for blood suppression [46]. Mitigation of swallowing artifacts was also proposed by Chan et al [47] using an electrical signal induced by motion of a coil placed on the neck to reject data acquired during swallowing. If the challenges of 3D imaging of artery walls can be overcome, 3D imaging also offers potential time efficiencies for certain imaging geometries.…”
Section: Imaging Technologymentioning
confidence: 99%